Polymer based flocculants: Review of water purification applications. (August 2022) - Abbasi Moud, Aref
Abstract: Water is an essential element contributing to human life. Evidence shows that only a portion of the water from sewage/tailings is recovered in the consolidated tailings process. The process produces sediments with a high-water content that require special storage. This is problematic because water trapped in such structures might remain there for a long period. This study investigates flocculants that can potentially help these systems. In this publication, we look at how literature has sought to optimise their formulation to enhance dewatering efficiency and present a clear overview and guidance on the main parameters involved, using both theoretical and practical examples. We have assembled over 200 references (majority published 2020 or earlier) in this review article to demonstrate the complexities of designing a flocculation system employing state-of-the-art synthesised, organic, inorganic, and hybrid flocculants. We next go over a few of examples of how to use microscopical techniques to learn more about the flocculation mechanism. This manuscript can be treated as an illustrative, visual, comprehensive view of application of flocculants to wastewater systems. Graphical abstract: Unlabelled Image Highlights: We have assembled over 200 references in this review article. Microscopical approaches have been review for flocculant-based systems. This manuscript can be viewed as a visual and comprehensive view of flocculants.